Answers

2016-03-20T18:09:52+05:30
     1            +       1            =   2 
---------------    ----------------     ----
(x - 1)(x - 2)   (x - 2)(x - 3)      3

    1    [     1     +     1     ]  =  2 -------------[Taken 1 / (x - 2) Common ]
-------   ---------    ---------      ----
(x - 2)   (x - 1)    (x  -  3)       3
   
   1     [x - 3 + x - 1]  = 2 
-------  ------------------  ----
(x - 2)  (x - 1)(x  -  3)   3
   
   1     [   2x - 4   ]   = 2 
-------   -------------     ----
(x - 2)  x² - 4x + 3      3
 
        2x - 4                   =  2
----------------------------     -----
x³ - 4x² - 2x²  + 3x - 6       3

        2x - 4             =  2
----------------------      -----
x³ - 6x² + 3x - 6         3

(2x - 4)3 = 2(x³ - 6x² + 3x - 6)
6x -12 = 2x³ -12x² +6x -12--[6x - 12 gets cancelled on both the sides]
2x³ - 12x² = 0
2x²( x - 6 ) = 0

2x² = 0  OR x - 6 = 0
x = 0     OR  x = 6

Sincerly Hope Answer is Correct
If Then,

Hope U Understood
Mark This Brainliest If This Helped You
Thankx
2 5 2
byb, why not 0? 0 is equally correct answer then
I got to know where i did the mistake but option of edit is not coming
0 and 4 is correct answer
there is no option of editing, unfortunately, anyway thanks for your time and efforts... i just wanted to verify my answer :)
I Thaught so Well That was understandable since u knew the answer be4 i wrote my answer